Understanding God images and God concepts: Towards a pastoral hermeneutics of the God attachment experience - Counted, Victor (Verbum et ecclesia, 2015)
The author looks at the God image experience as an attachment relationship experience with God. Hence, arguing that the God image experience is borne originally out of a parent child attachment contagion, in such a way that God is often represented in either secure or insecure attachment patterns. The article points out that insecure God images often develop head-to-head with God concepts in a believer s emotional experience of God. On the other hand, the author describes God concepts as indicators of a religious faith and metaphorical standards for regulating insecure attachment patterns. The goals of this article, however, is to highlight the relationship between God images and God concepts, and to provide a hermeneutical process for interpreting and surviving the God image experience.Intradisciplinary and/or interdisciplinary implications: Given that most scholars within the discipline of Practical Theology discuss the subject of God images from cultural and theological perspectives, this article has discussed God images from an attachment perspective, which is a popular framework in psychology of religion. This is rare. The study is therefore interdisciplinary in this regards. The article further helps the reader to understand the intrapsychic process of the God image experience, and thus provides us with hermeneutical answers for dealing with the God image experience from methodologies grounded in Practical Theology and pastoral care.